2014
DOI: 10.1080/09168451.2014.882748
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-homoserine lactones suppresses IEC-6 cell proliferation and increase permeability of isolated rat colon

Abstract: We investigated to determine whether a variety of acyl-homoserine lactones (AHLs) influences epithelial cell proliferation and mucosal permeability. 3-Oxo-C12-homoserine lactone (HSL) and 3-oxo-C14-HSL significantly suppressed IEC-6 cell proliferation. A significant increase in mucosal permeability was observed in isolated rat colon tissue exposed to C12-HSL, 3-oxo-C12-HSL, and 3-oxo-C14-HSL. These data indicate that AHLs suppress epithelial proliferation and disrupt barrier function in intestinal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…7) However, we previously found that relatively low concentrations of 3-oxo-C 12 -HSL between 10 and 30 μM can induce the apoptosis of undifferentiated Caco-2 cells, and increase the mucosal permeability of the isolated rat colon. 8,9) Similar levels of 3-oxo-C 12 -HSL can be generated in culture supernatants of the P. aeruginosa PT149 strain without biofilm formation. 10) Therefore, 3-oxo-C 12 -HSL can affect intestinal epithelial cells at much lower concentrations than those found in biofilms.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…7) However, we previously found that relatively low concentrations of 3-oxo-C 12 -HSL between 10 and 30 μM can induce the apoptosis of undifferentiated Caco-2 cells, and increase the mucosal permeability of the isolated rat colon. 8,9) Similar levels of 3-oxo-C 12 -HSL can be generated in culture supernatants of the P. aeruginosa PT149 strain without biofilm formation. 10) Therefore, 3-oxo-C 12 -HSL can affect intestinal epithelial cells at much lower concentrations than those found in biofilms.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…Notably, quorum sensing was previously considered to be a bacteria-to-bacteria signaling mechanism to shape community structure, but now there is evidence indicating that QS may also be involved in the inter-kingdom signaling among symbiotic microbiota, pathogenic microbiota and the host [64][65][66]. Examples include a host synthesis of QSmimics to communicate with bacteria [67] and host responses to bacterial QS signals [68][69][70]. Moreover, bacteria have also been reported to sense and respond to host signals (e.g., hormones [71]).…”
Section: Figure 2b and 2cmentioning
confidence: 99%